The Impact of Halal Nutrition on Student Morality - Pg Metusin , Pg Norwidayawati (Journal of Social Transformation and Regional Development, 2021)
The practice of halal diet in daily life is very important in meeting the demands of religion and also daily life based on Halalan Tayyiban. This food selection, if practiced, can certainly have a profound effect on one’s morals. This study aims to identify the moral impact of secondary school students in Brunei Darussalam through the practice of halal nutrition in daily life through four elements of morality, namely morality to oneself, morality to parents, morality to teachers, and morality to society. This study uses the design of survey research (Explanatory Research) through the quantitative method, which is descriptive by providing a questionnaire to 790 Year 9 secondary school students randomly selected. Overall, these descriptive findings indicate that the four moral elements are at a high level, namely (mean = 4.23, sp = 0.50). In conclusion, good morals can be formed through the practice of halal eating, because halal eating will form a clean and pure heart. To further strengthen the practice of halal nutrition in students continuously, it is proposed that halal food education be established in secondary schools in Brunei Darussalam through Islamic religious knowledge subjects. Through halal food education, it will further increase the understanding, the practice of students on halal food and at the same time make it a culture in their lives when choosing food. Therefore, by adopting a halal diet, one will become a healthier person physically, mentally, and spiritually.